PROBLEMATIC SMARTPHONE USE IN ADOLESCENTS: PARENTAL STRUCTURE AND PARENTAL PSYCHOLOGICAL CONTROL AS PREDICTORS - Lathiifah, Dwi Astrifiani; Qodariah, Laila; Abidin, Fitri Ariyanti (Jurnal Ilmu Keluarga dan Konsumen, 2023)
The use of smartphones in adolescents can negatively impact their daily lives. When adolescents’ ability to control smartphone use is low, they could experience problematic smartphone use behavior (PSU). By internalizing control, parents play a crucial role in enhancing adolescents' self-control on smartphone use. Based on the controlling component of parenting, there are two types of parental control: parental structure and parental psychological control. Previous studies have found a relationship between parental psychological control and PSU. However, studies investigating the relationship between parental structure and parental psychological control simultaneously with PSU are limited. This study is important since parents found practicing those two types of parental control simultaneously. Therefore, this study aimed to investigate the effect of parental structure and psychological control on adolescents' problematic smartphone use. 219 adolescents aged 12-18 (M = 14.49 years) completed the Indonesian version of the Parental Structure Scale, Parental Psychological Control Scale, and Mobile Phone Problematic Use Scale questionnaires. Stepwise regression analysis shows that only parental psychological control predicts the increase of problematic smartphone use in adolescents. Our finding suggested that the type of parental control that emphasizes authority assertion, love withdrawal, and guilt induction is ineffective in decreasing problematic smartphone use in adolescents.